Evaluation of a Virtual Team-Based Project Designed to Improve Chronic Wound Patient Care in Ontario, Canada. (5th August 2022) - Fan, Angela; Elliott, James A.; Jaimangal-Persaud, Reneeka; Soleas, Eleftherios K.; Smith, Karen; Mohan, Andrew; Wicher, Camilla; Sibbald, R. Gary
ABSTRACT: OBJECTIVE: To evaluate the effectiveness of the Extension for Community Healthcare Outcomes Ontario Skin and Wound Care project, a virtual team-based endeavor designed to improve the care of patients with chronic wounds. METHODS: The study team conducted phone interviews with healthcare professionals (n = 8) regarding their patients (n = 10). The management recommendations were grouped, and the study participants questioned concerning the implementation of the recommendations. Interviews were recorded and transcribed, and the transcripts were analyzed for common themes. The Queen's University Research Ethics Board approved this study. RESULTS: Interviews documented improvement in 50% of patients; the other half of the patients did not improve because of patient- and healthcare-system barriers. Three of five nonhealing patients were nonadherent regarding compression, and only one of six suggested biopsies were carried out. The investigators noted three primary reasons for the lack of recommendation implementation: (1) could not obtain a diagnostic procedure, (2) lack of a diagnosis, and (3) patient was reluctant to make a lifestyle change. Major themes included problems in care coordination and suboptimal patient and provider education, along with other obstacles to management. CONCLUSIONS: Participants stated that the project provided a beneficial learning experience. The findings highlighted a lack of integrated and coordinated interprofessional chronic wound care.